A method to ingest GPS-TEC into the NeQuick ionospheric model - Brunini, Claudio Antonio (2007)
This paper presents a method to ingest Total Electron Content measurements from ground-based GPS receivers into the empirical NeQuick model. The method here presented relies upon optimizing the parameter that primarily drives the NeQuick profile, i.e., the electron density of the F2 peak, NmF2. The effectiveness of the method is assessed in a rather benevolent ionospheric scenario: a midlatitude region and quiet geomagnetic days that cover solstices and equinoxes conditions during a medium-high solar activity year. Thus, the procedure demonstrated to be capable of improving the climatological value of NmF2 computed from the Radioscience Section of the International Telecommunication Union (ITU-R) database. This capability was assessed by comparing the ITU-R value and the corrected value produced by our method to the value measured with a Digisonde. The result of this comparison was an overall reduction of the error of the NmF2 parameter to approximately half of its original value.